Da dimensão humana à literatura de autoajuda: reflexões sobre a formação e o trabalho docente - Arnosti, Rebeca Possobom [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research considers there is a sales phenomenon with the self-help literature (SL). In this segment, increases the production of books focused on education. Based on this, the following questions were elaborated: Do teachers really seek this literature? The self-help literature gives opportunities to the development of teaching practices and the teachers training? This study aim to (a) investigate how the SL has been debated in scientific research; (b) identify the motivations that lead teachers to consume the self-help literature; (c) verify how teachers use SL in their school life; (d) ascertain if the teachers feel the school support in the human dimension and in its training. 271 teachers from Rio Claro's public schools answered a questionnaire. Three focus groups were performed with 12 questionnaires respondents. Data were analyzed by Prose Analysis. Referring to the first aim, 19 researchs on LA were found in the Biblioteca Digital Brasileira de Teses e Dissertações. These highlighted its sales success, analyzing the speech of books, the meanings produced by readers or relations between books and historical and social conditions. Referring to the second aim, 227 teachers said they had read at least one self-help book, the most cited books: Bright Parents and Fascinating Teachers and Those who love, educate!. Different reading motivations were presented: indications from friends; indications from a teachers training institution or from school; interest by title / author / topic / genre; search for personal life contributions (especially spiritual empowerment), search for profession contributions and better human interactions. Thinking about the third aim, 168 participants presented SL contributions to personal life and 158 to teaching: SL helps in the personal dimension; in training and in work (mainly it helps to understand and deal with human interactions); besides the books were used as work tools. However, their...

Esta pesquisa considera o significativo consumo da literatura de autoajuda (LA) entre os docentes, questionando se tal leitura se relacionar a desafios inerentes à formação e ao trabalho docente. Assim, objetivamos: (a) investigar como a literatura de autoajuda vem sendo tratada na pesquisa científica; (b) identificar os motivos pelos quais a literatura de autoajuda vem sendo consumida pelos professores da Educação Básica - ciclo I; (c) apresentar a relação que os professores estabelecem entre a literatura de autoajuda e o seu trabalho docente; (d) averiguar se os professores se sentem amparados pela escola frente à dimensão humana e à sua formação. 271 professores da rede pública municipal de Rio Claro- SP participaram deste estudo qualitativo respondendo a um questionário. Três grupos focais foram realizados com 12 respondentes dos questionários. Os dados foram analisados segundo a análise de prosa. Referindo-se ao primeiro objetivo, 19 pesquisas sobre a LA foram encontradas na Biblioteca Digital Brasileira de Teses e Dissertações. Essas destacavam seu sucesso de vendas, analisavam o discurso dos livros, os sentidos produzidos pelos leitores ou relações estabelecidas entre os livros e condições histórico-sociais. Remetendo ao segundo objetivo, 227 professores afirmaram ter lido ao menos um livro de autoajuda, sendo os livros mais citados: Pais brilhantes, professores fascinantes e Quem ama educa. Diferentes motivações para a leitura foram apresentadas: indicações de um conhecido; indicações de uma instituição formadora de professores ou da escola; interesse pelo título/autor/temática/gênero; busca de contribuições às interações humanas; à vida pessoal, (especialmente fortalecimento espiritual); à profissão. Pensando no terceiro objetivo, 168 destacaram contribuições da LA à vida pessoal e 158 à docência: os livros auxiliaram na dimensão pessoal; na formação e no trabalho docente...
Keywords: Teachers, Traininf of; Professores - Formação; Autoajuda; Literatura; Identidade profissional